A partial lubrication model between valve plate and cylinder block in axial piston pumps. (December 2015) - Han, Lei; Wang, Shaoping; Zhang, Chao
Axial piston hydraulic pumps are commonly used in aircraft, which makes analysis of their lubrication conditions of significant importance. Oil film between valve plate and cylinder block plays an most important role in pump lubrication. This paper proposes a partial lubrication model of the contact surfaces between valve plate and cylinder block in axial piston pumps for predicting film thickness. The asperity curvature at multiple scales and height distribution are obtained by analyzing actual contact surface profiles, then the separating pressure of asperities is estimated by the Hertz theory and the fluid separating pressure is calculated by Reynolds equation. Experimental results indicate that this model can predict film thickness accurately.